Examining The Characteristics Of Academic Entrepreneurs: The Case Of Malaysian Technology Driven University - Ahamat, Amiruddin; Mohamad Sharif, Sabri; Masrom, Nor Ratna; Che Aziz, Che Nurul Azni; Shahkat Ali, Muhamad Sham (Penerbit UTHM, 2021)
With resources of MYR 564 million being invested on research and development in 2020 by the Malaysia government, it is crucial for Malaysian universities to develop an entrepreneurial ecosystem among academia. This is more significant among technical driven universities. The aim of this study is to examine the various factors that lead technology researchers to recognise and create opportunities. The case study is derived from one of Malaysia’s technology driven universities. This research adopts a qualitative method in which the data were collected from nine lecturers and researchers who were actively involved in creating innovative products and services. Semi-structured interviews and observational methods were employed with six of the respondents. In this study, an exploratory research is selected to ask open questions, in order to find out the challenges and processes of academia in shaping entrepreneurial characteristics. Qualified respondents that is directly involved in the subject of study is selected. These participants are selected academics and researchers from technology management and engineering academic backgrounds. The findings show that networking was used to get resources, and opportunities were from the policy or government interventions and events such as seminars and conferences. Most of the respondents indicate that events are great opportunities to connect with the industry and external parties. Through extensive networking, technology researchers can build various programs for new researchers so that they realize the importance of opportunities, especially in the field of technology, as it is now booming. The implication of this study reflects the university’s effort that can be viewed from the case, where self-efficacy and risk taking can be further promoted among academics who are moving from research to business venture. For the study to be conducted in the future, the researcher suggests the need to obtain a better understanding of conditions of uncertainty which shape opportunity creation and the scope of the research must be extended to other aspects. Future research should also include other institutions to see clearly the role of opportunity creation and the challenges faced by them.